2021
DOI: 10.3390/su13147865
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Energy Management and Charging Strategy for Electric Bus Fleets in Cities Using Various ECO Strategies

Abstract: The paper presents use case simulations of fleets of electric buses in two cities in Europe, one with a warm Mediterranean climate and the other with a Northern European (cool temperate) climate, to compare the different climatic effects of the thermal management strategy and charging management strategy. Two bus routes are selected in each city, and the effects of their speed, elevation, and passenger profiles on the energy and thermal management strategy of vehicles are evaluated. A multi-objective optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…A significant peak load reduction can be achieved by adding an ESS to an opportunity charger, but the additional space requirements make this solution of course not possible for every charger in the city. The results of Hasan et al [90] are more promising, even though this requires a longer charging time, and thus also a longer waiting time, at the end terminals, while this is not always possible due to delays. Nevertheless, smart charging can become critical for a citywide deployment of high-power chargers.…”
Section: Synchronized Opportunity Chargingmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant peak load reduction can be achieved by adding an ESS to an opportunity charger, but the additional space requirements make this solution of course not possible for every charger in the city. The results of Hasan et al [90] are more promising, even though this requires a longer charging time, and thus also a longer waiting time, at the end terminals, while this is not always possible due to delays. Nevertheless, smart charging can become critical for a citywide deployment of high-power chargers.…”
Section: Synchronized Opportunity Chargingmentioning
confidence: 99%
“…Moreover, in [88,89], the authors used an ESS to minimize the total charging cost and reported that it could contribute to a cost reduction of up to 15% and 22%, respectively. A study conducted by Hasan et al [90] for the European project, ASSURED, attempted to determine the impact on the grid due to the deployment of high-power opportunity chargers for public transport networks. The study found that utilizing a pulsed charging method reduced vehicle energy requirements by up to 18% and reduced peak grid loads by 10% or more.…”
Section: Charging Managementmentioning
confidence: 99%
“…In some countries like the Netherlands, EV integration reaches the limit in most of the DSO connection points [12][13][14]. In the ASSURED project, among several demos, there are more than 43 HD e-buses integrated in the Eindhoven demo, which will be upscaled to 200 HD e-buses [9]. Smart charging, besides RES, is a promising solution to address the congestion in the DSO grid and maintain the reliability and security of supply with some financial benefits, which could be a motivation to adopt this technology.…”
Section: E-bus Fleet Impact On the Power Gridmentioning
confidence: 99%
“…e-buses integrated in the Eindhoven demo, which will be upscaled to 200 HD e-buses [9]. Smart charging, besides RES, is a promising solution to address the congestion in the DSO grid and maintain the reliability and security of supply with some financial benefits, which could be a motivation to adopt this technology.…”
Section: Uncoordinated Charging (Standard Charging)mentioning
confidence: 99%
See 1 more Smart Citation